A Modified Hexagonal Pyramidal InP nanowire Solar Cell structure for Efficiency Improvement: Geometrical Optimisation and Device Analysis. (1st May 2022) - Kumar Agnihotri, Suneet; Prashant, D.V.; Samajdar, D.P.
Highlights: Performance of InP nanostructured based Solar Cell (SC) is studied using FDTD method. Three different nanostructures: nanowire (NW), nanopyramid (NP) and a combination of NW and NP are investigated. PCE of ∼ 23 % is achieved with p-i-n junction for our proposed InP Hybrid hexagonal pyramidal nanowire (HHPNW) SC. Abstract: Vertically stacked nanostructure arrays are considered as promising candidates for photovoltaic (PV) applications. High absorption and excellent carrier collection efficiency along the axial direction with reductions in reflection and transmission losses have contributed significantly to increasing the efficiency of nanostructure-based InP solar cells (SCs). We investigated the optical and electrical behaviour of three distinct InP nanostructure geometries in this paper: hexagonal nanowire (HNW) SC, hexagonal nanopyramid (HNP) SC, and our proposed Hybrid hexagonal pyramidal nanowire (HHPNW) SC. The optimisation of the geometrical parameters of InP nanostructures grown on an InP substrate, such as diameter (D), period (p), and filling ratio (FR), offers a wide range of variations of the optical and device characteristics as a function of structural morphology. Finite Difference Time Domain (FDTD) simulation of HNW, HNP, and HHPNW structures reveals that our proposed HHPNW SC has a higher generation rate, better absorption, and higher optical short circuit current density ( Jsc ) of 34.2 mA/cm 2 than the HNW (32.5 mA/cm 2 ) and HNP (32.86 mA/cm 2 ). The generation rate profile of all optimised nanostructures is transferred to Lumerical's Device Charge Solver module to investigate the electrical analysis in terms of PV parameters namely electrical Jsc, open-circuit voltage ( Voc ), Fill Factor ( FF ), and Power conversion efficiency ( PCE ). In the electrical analysis, we performed a comparative analysis of the p-n junction and p-i-n junction for all three structures under consideration, and it was observed that our proposed structure, InP HHPNW, outperforms the InP HNW and InP HNP with a conversion efficiency of 19.15 % and 23% for p-n and p-i-n junction, respectively.